Long-Term Risk of Death From Heart Disease Among Breast Cancer Patients - Agha, Aya; Wang, Xi; Wang, Ming; Lehrer, Eric J.; Horn, Samantha R.; Rosenberg, Jennifer C.; Trifiletti, Daniel M.; Diaz, Roberto; Louie, Alexander V.; Zaorsky, Nicholas G. (Frontiers in Cardiovascular Medicine, 2022)
Background: Most breast cancer patients die of non-cancer causes. The risk of death from heart disease, a leading cause of death, is unknown. The aim of this study is to characterize the long-term risk of fatal heart disease in breast cancer patients. Methods: This retrospective study used the Surveillance, Epidemiology, and End Results (SEER) database. Standard mortality ratios (SMR) were calculated for breast cancer patients diagnosed from 1992-2014. Patients were stratified by receipt of radiotherapy and/or chemotherapy, disease laterality, and diagnosis era. Hazard ratios (HRs) and odds ratios (ORs) were calculated to compare the risk of death from heart disease among other breast cancer patients. Results: There were 1,059,048 patients diagnosed with breast cancer from 1992-2014, of which 47,872 (4.6%) died from heart disease. The SMR for death from heart disease at 10+ years for patients who received only radiotherapy was 2.92 (95% CI 2.81–3.04, p<0.001) and in patients who received only chemotherapy was 5.05 (95% CI 4.57–5.55, p<0.001). There was no statistically significant difference in SMR for death from heart disease for left-sided vs. right-sided disease. At 10+ years, heart disease made up 28% of deaths from non-primary cancer. HRs and ORs showed that the risk of death from heart disease was highest in patients older than 70 years of age and with longer follow up. Conclusion: The risk of fatal heart disease was highest in older breast cancer patients with longer follow-up (i.e. >5-10 years) and who received chemotherapy. These patients should be referred to cardio-oncology clinics to mitigate this risk. Keywords: Cardio-oncology; radiotherapy; breast cancer; heart disease; chemotherapy